Determination of heavy metals in varieties of fresh and packaged fruit juices along with powdered fruit drink mixes in Kathmandu Valley - Subedi, Sabita; Adhikari, Dipendra; Poudel, Bhoj Raj (Journal of Balkumari College, 2022)
Analysis of heavy metals was performed in packaged and fresh fruit juices along with powdered fruit drink mixes (Tangs), purchased from different stores of Kathmandu Valley, using Flame Atomic Absorption Spectroscopy (FAAS). Selection of Fruit Juices and Tangs was done from five different fruits, viz., apple, orange, pineapple, pomegranate, and mango in an attempt to quantify four heavy metals, i.e., Zinc (Zn), Manganese (Mn), Iron (Fe) and Lead (Pb). The wet digestion technique was employed for the decomposition of samples. Variability in the concentration of heavy metals was observed in various types of fruit juices, thereby verifying that the levels of heavy metals are dependent on the types of fruits as well as fruit juices. The mean concentrations of all the investigated metals (Fe, Pb, Mn, and Zn) were below the maximum permissible limit in the selected juices and tangs. Irrespective of the types of fruits or nature of juices, i.e., either packaged or fresh fruit juices or tangs, the studied samples are safe for human consumption based on studied heavy metals toxicity.